The combination of cognitive and language human abilities in the concept of A. A. Potebnya - Палатовская, Елена Владимировна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The paper presents the interpretation of views of A.A. Potebnya on combination of language and thinking from the perspective of the latest cognitive research. The article examines the key issues of the theory of the scientist: the nature and evolution of language, its participation in the formation, storage and transmission of ideas, correlation between a though and its expression in the language. The article also explores the relation between the views of the scientist and views of modern cognitive linguists and identifies obvious parallels.